2006
DOI: 10.1038/sj.onc.1209323
|View full text |Cite|
|
Sign up to set email alerts
|

Fhit modulation of the Akt-survivin pathway in lung cancer cells: Fhit-tyrosine 114 (Y114) is essential

Abstract: The Fhit tumor suppressor binds and hydrolyses diadenosine polyphosphates and the Fhit-substrate complex has been proposed as a proapoptotic effector, as determined by infection of susceptible cancer cells with adenoviruses carrying wild-type fragile histidine triad (FHIT) or catalytic site mutants. The highly conserved Fhit tyrosine 114 (Y114), within the unstructured loop C-terminal of the catalytic site, can be phosphorylated by Src family tyrosine kinases, although endogenous phospho-Fhit is rarely detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 39 publications
1
70
1
1
Order By: Relevance
“…Inactivation of the phosphatidylinositol 3-kinase/Akt/survivin pathway by Fhit is also implicated in Fhit-mediated apoptosis signaling (20). We assessed previously the Atr-Chk1 pathway in response to mitomycin C, UVC, and ionizing radiation in Fhit-positive and Fhit-negative cells and found that Fhitnegative cells are resistant to apoptosis induced by these genotoxic agents despite activation of the Atr-Chk1 pathway (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inactivation of the phosphatidylinositol 3-kinase/Akt/survivin pathway by Fhit is also implicated in Fhit-mediated apoptosis signaling (20). We assessed previously the Atr-Chk1 pathway in response to mitomycin C, UVC, and ionizing radiation in Fhit-positive and Fhit-negative cells and found that Fhitnegative cells are resistant to apoptosis induced by these genotoxic agents despite activation of the Atr-Chk1 pathway (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture and Treatment H1299 human lung carcinoma cells (lacking Fhit expression) obtained from the American Type Culture Collection (Manassas, Adenoviruses carrying human recombinant wild-type (Ad-FHIT-wt) and Y114 mutant FHIT substituted with phenylalanine (Ad-FHIT-Y114F) were used in this study (14,20). Briefly, wild-type and mutant FHIT cDNA were cloned into the transfer vector pAdenoVator-CMV5-GFP (Qbiogene, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…43,44 Most recent, it has bee shown that FHIT modulates the Pi3k/AKT pathway by downregulation of the antiapoptotic survivin, an inhibitor of apoptosis protein (IAP) family member. 45 Our data indicate that inactivation of FHIT might be due to different reasons. A comparison of expression data as observed by immunohistochemistry and promotor hypermethylation did not show a significant association.…”
Section: Discussionmentioning
confidence: 72%